Repopulation of tumor cells during fractionated radiotherapy and detection methods (Review) - YANG, JIA (D.A. Spandidos, 2014)
Repopulation of tumor cells during radiotherapy is believed to be a significant cause for treatment failure. The phenomenon of tumor repopulation during fractionated radiotherapy was found from clinical observations that identified that the local control rate decreased with a prolonged treatment time. A series of animal experiments with varied overall treatment time and fractionated doses were performed to demonstrate tumor cell repopulation during radiotherapy in various mouse xenograft models. However, conventional detection methods are challenging, as it is difficult to separate viable cells from those destined for apoptosis during fractionated radiotherapy. In essence, the mechanism of tumor repopulation involves the continuing proliferation of clonogenic tumor cells. In vivo imaging, tracking and targeting of the repopulation of these cells has been of clinical interest so as to administer a higher dose to the tumor repopulation regions. Currently, functional imaging methods, including 3′-deoxy-3′-(18)F-fluorothymidine positron emission tomography ((18)F-FLT PET), are showing promise in assessing the proliferation activity of tumors in vivo. This review mainly focuses on the phenomenon of tumor repopulation during radiotherapy and its conventional and novel detection methods, particularly on the feasibility of (18)F-FLT PET for the detection of tumor-cell repopulation.